Features of Crohn's Disease Depending on the Age of Disease Onset - E. G. Ganich; O. B. Shchukina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to evaluate the characteristics of Crohn's disea depending on the age of the disease onset in patients observed in a specialized City Center for Inflammatory Bowel Diseases Diagnosis and Treatment.Materials and methods. We observed 180 patients with an established diagnosis of Crohn's disease for 52 weeks, followed by a retrospective assessment. Patients were divided into three groups depending on the age of the onset of the disease according to the Paris classification (A1, A2, A3). The visits included: the collection of complaints, medical history, objective examination, clinical blood testing; biochemical blood testing (C-reactive protein); fecal calprotectin; ileocolonoscopy. Statistical processing of the obtained data was carried out using Excel, RStudio and the R language; for categorical data, the Pearson chi-square test or Fisher's exact test was used (for 2 × 2 tables with small samples). For categorical and quantitative, the Mann – Whitney t-test was used. Student's t-test was used to test the equality of means.Results. The gender distribution and the average duration of the disease were comparable in all groups. At the time of diagnosis, ileocolitis (p = 0.01), inflammatory form of Crohn's disease (p < 0.05), and the upper gastrointestinal tract involvement (p < 0.05) were more frequently detected in group A1. Isolated colonic Crohn’s disease predominated in group A3 (p < 0.001). No significant difference between the groups in the incidence of extraintestinal manifestations of the disease was found (p = 0.32). In group A1, there was a positive correlation between smoking and lack of response to therapy. In group A2, endoscopic remission was observed less frequently among smokers at the end of the study (p < 0.05). Anal fissures were noted as the most common perianal disease in all groups. In group A1, there was a positive correlation between clinical, laboratory and endoscopic remission and the absence of perianal disease. At the end of the follow-up, the worsening of endoscopic SES-CD level was observed more frequently in the patients with the onset before 30 years old in group A2 (p = 0.01).Conclusions. Not only pediatric onset, but also the onset of Crohn's disease before the age of 40 is a risk factor for the progression of the disease and its more severe course.